Real-time reconstruction of the strong-field driven dipole response. Issue 9 (January 2020) - Stooß, V; Cavaletto, S M; Donsa, S; Blättermann, A; Birk, P; Keitel, C H; Březinová, I; Burgdörfer, J; Ott, C; Pfeifer, T
Synopsis: Using ultrashort and phase-locked laser pulses, combined with an in situ measurement of a reference pulse, we present a method capable of retrieving the nonlinearly perturbed time-dependent response function of a quantum system driven by strong electric fields directly from spectroscopic absorption data with high precision.